2012
DOI: 10.1200/jco.2011.34.6270
|View full text |Cite
|
Sign up to set email alerts
|

BEAM: A Randomized Phase II Study Evaluating the Activity of Bevacizumab in Combination With Carboplatin Plus Paclitaxel in Patients With Previously Untreated Advanced Melanoma

Abstract: A B S T R A C T PurposeMetastatic melanoma, a highly vascularized tumor with strong expression of vascular endothelial growth factor, has an overall poor prognosis. We conducted a placebo-controlled, double-blind phase II study of carboplatin plus paclitaxel with or without bevacizumab in patients with previously untreated metastatic melanoma. Patients and MethodsPatients were randomly assigned in a two-to-one ratio to carboplatin (area under the curve, 5) plus paclitaxel (175 mg/m 2 ) and bevacizumab (15 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 32 publications
7
134
1
2
Order By: Relevance
“…Because VEGF expression has been shown to play a role in metastatic melanoma (43), studies to explore the combination of carboplatin, paclitaxel, and antiangiogenic agents such as sorafenib and bevacizumab have been performed; however, these studies have not shown improved efficacy compared with the carboplatin and paclitaxel doublet (30,42). In this study, the response rate for melanoma was 29% (5 of 17 patients with PR) with an additional 41% (7 of 17 patients) demonstrating SD of >12 weeks, and one patient diagnosed with ocular melanoma maintained antitumor response for more than 100 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because VEGF expression has been shown to play a role in metastatic melanoma (43), studies to explore the combination of carboplatin, paclitaxel, and antiangiogenic agents such as sorafenib and bevacizumab have been performed; however, these studies have not shown improved efficacy compared with the carboplatin and paclitaxel doublet (30,42). In this study, the response rate for melanoma was 29% (5 of 17 patients with PR) with an additional 41% (7 of 17 patients) demonstrating SD of >12 weeks, and one patient diagnosed with ocular melanoma maintained antitumor response for more than 100 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel has been used in the first-line treatment of metastatic melanoma both as a single agent and in combination with carboplatin, with reported response rates of approximately 12% to 16% (38)(39)(40) and 16% to 20%, respectively (30,41,42). Because VEGF expression has been shown to play a role in metastatic melanoma (43), studies to explore the combination of carboplatin, paclitaxel, and antiangiogenic agents such as sorafenib and bevacizumab have been performed; however, these studies have not shown improved efficacy compared with the carboplatin and paclitaxel doublet (30,42).…”
Section: Discussionmentioning
confidence: 99%
“…We did not enroll patients in the clinical subgroups where these mutations are found. The efficacy of bevacizumab has been explored in combination with carboplatin/paclitaxel in a randomized phase II trial of patients with metastatic melanoma [52]. Marginal and statistically nonsignificant improvements in progression-free survival were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab is a monoclonal antibody that can selectively bind VEGF and block its binding with receptors. It has been widely applied in the treatment of metastatic melanoma (182)(183)(184)(185). In a randomized, double-blind phase II study (BEAM study), 214 metastatic melanoma patients were randomized into carboplatin + paclitaxel + bevacizumab (CPB) group or placebo group (CP) at a proportion of 2:1.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%